Characterization of Structural and Functional Flexibility in Herpesvirus Outer Tegument Proteins - Metrick, Claire. (2018)
Abstract: Herpesviruses are large, enveloped, DNA viruses that infect nearly all vertebrates from fish to humans and cause diseases ranging from mild to fatal. They are morphologically complex and sandwiched between their genome-filled capsid and glycoprotein-studded envelope, herpesviruses feature a dynamic layer of viral proteins called the tegument. Tegument proteins play important structural roles in virion morphogenesis, but a detailed understanding of how these proteins operate is lacking. It is also becoming clear that many tegument proteins play regulatory roles in addition to their canonical functions in viral structure and assembly. Herpes simplex virus type 1 (HSV-1) UL11 is the smallest tegument protein. It is conserved among all herpesviruses and is found associated with cytoplasmic membranes through acyl modifications at its N-terminus. UL11 binds UL16, a tegument protein in HSV-1 that is also completely conserved. As UL16 binds capsids in the cytoplasm, the interaction between these two proteins is thought to form a physical link between the capsid and the envelope and play a structural role in secondary envelopment, the step of viral maturation and egress in which nucleocapsids gain their final envelope. In HSV-1, this interaction requires tegument protein UL21. UL21 is conserved among alphaherpesviruses and is found in the cytoplasm and nucleus in transfected and infected cells. With capsid-associated UL21, UL16 and UL11 bind glycoprotein E, forming an even more stable link between the capsid and the envelope. HSV-1 UL51 is another conserved tegument protein that is associated with membranes by lipid modification. It too is thought to play structural roles in virion morphogenesis through interactions with conserved tegument proteins UL7 and UL14 and glycoprotein E to affect secondary envelopment. In addition to these structural roles that are not completely understood, there is evidence that UL11, UL16, UL21, and UL51 also function independently of their complexes. To provide context for exploration of the multiple roles of these proteins, we have characterized them structurally and biochemically. In addition to determining the crystal structures of HSV-1 UL21 domains, which revealed novel protein folds, we have characterized each of these proteins as being conformationally flexible, which likely contributes to their multifunctionality. Current work focuses on carefully characterizing binding interactions, including two novel interactions with nucleic acids, and assessing their structural implications to better unravel the mechanisms of the many functions these proteins play during viral replication.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Biochemistry.; Advisor: Ekaterina Heldwein.; Committee: Andrew Bohm, Michael Forgac, Claire Moore, and Thomas Schwartz.; Keywords: Biochemistry, Biophysics, and Microbiology.